116 THE TRANSCRIPTIONAL REPRESSOR ZINC-FINGER E-BOX BINDING PROTEIN TARGETED BY HYPOXIA-INDUCIBLE FACTOR-1a IN RESPONSE TO STROKE REPRESSES A NUMBER OF PROAPOPTOTIC GENES. (1st January 2006) - Genetta, T.; Wen, T. -C.; Sequeira, J.; Priani, A.; Wu, H.; Feng, G.; Sola, A.
Abstract : We have recently discovered that a transcriptional repressor protein called ZEB (zinc-finger E-box binding protein), thought to be involved in regulating the timing and spatial boundaries of neurogenic determination/differentiation programs, can function to promote neuronal cell survival against a number of proapoptotic insults, including hypoxia-ischemia (H-I). ZEB protein levels increase dramatically in pyramidal cells of the rat cerebral cortex in response to experimentally administered unilateral focal cerebral ischemia [FCI: 15-fold (postnatal day 7) and 30-fold (8 week adult), compared to the contralateral control]. We show that not only is ZEB a HIF-1a transcriptional target, but in response to H-I, it represses several classes of genes involved in either mediating neuronal apoptosis or in inhibiting HIF-1a-induced survival pathways. Further, we present evidence that, for a subset of these proapoptotic genes, notably PUMA, BMF, etc, ZEB is acting through TAp73 and its truncated isoform, DNp73. Lastly, we show that immunostained paraffin sections derived from archived samples of cortical brain taken at autopsy from human perinatal stroke patients give nearly identical results, with respect to intensity and staining pattern, of ZEB protein induction as seen in our experimental model of permanent FCI. Funded through the Emory Goddard Scholar Award (A.S.) and the United Cerebral Palsy Research Foundation (T.G.).